If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + 7 = 5y + -2 Reorder the terms: 7 + 6y = 5y + -2 Reorder the terms: 7 + 6y = -2 + 5y Solving 7 + 6y = -2 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 7 + 6y + -5y = -2 + 5y + -5y Combine like terms: 6y + -5y = 1y 7 + 1y = -2 + 5y + -5y Combine like terms: 5y + -5y = 0 7 + 1y = -2 + 0 7 + 1y = -2 Add '-7' to each side of the equation. 7 + -7 + 1y = -2 + -7 Combine like terms: 7 + -7 = 0 0 + 1y = -2 + -7 1y = -2 + -7 Combine like terms: -2 + -7 = -9 1y = -9 Divide each side by '1'. y = -9 Simplifying y = -9
| -1/2x+1/8=-1/3x+1/4 | | u=v-8 | | (2-5i)(-2+5i)= | | 3a+14=41 | | Z=q-qx | | 2x*x-8=31x-2x*x | | Q=Q-Qx | | 51=x^2+21x | | 6x+29=5/x | | (2(cos^2(x)))+(6(cos(x)))=1 | | -16=(c-6/-3) | | c/6+2=5 | | -10=(a+3/3) | | 4x-18=-62 | | (s-8/-8)=-1 | | x^2-9x+2=24 | | (f-6/5)=0 | | (5+r/-2)=-6 | | 3(x-7)=-4(x-7) | | (t+2/5)=-5 | | (t+2/5)=0 | | -11+z/6+0 | | 5(3+x)=35 | | (2x+3)(x-7)= | | 2r^2-14r+24=0 | | -5/5-3=17 | | f(x)=x^4-4x^3+3x^2 | | 9x^2-9x-3=0 | | 2w-3=1 | | 2(x+6)=2(x*x) | | 2n^2+n-3=0 | | 6x^2=-216 |